External Validation of Equations that Use Demographic and Anthropometric Measurements to Predict Percent Body Fat. (2nd November 2018) - Reynolds, K. R.; Stevens, J.; Cai, J.; Lewis, C. E.; Choh, A. C.; Czerwinski, S. A.
Summary: Objective: Numerous equation to predict percent body fat using demographics and anthropometrics have been published but external validation of these equations is limited. The objective of this study was to validate published equations that use anthropometrics for prediction of percent body fat using external data. Methods: Data were from the Visceral Fat, Metabolic Rate, and Coronary Heart Disease Risk I (VIM I) Study and the Fels Longitudinal Study (Fels). VIM I was conducted in a subset of subjects from the CARDIA study and included black and white adults 28–40 years ( n = 392). Fels consisted of white participants 8–88 years ( n = 1, 044). Percent body fat assessed by dual X‐ray absorptiometry (DXA) in these two studies was compared to results calculated using 13 equations from Stevens et al. and nine other published equations. Results: In general, the Stevens equations performed better than equations from other studies. For example, equation "I" in women in VIM I, Fels adults, and Fels youth, R 2 estimates were 0.765, 0.757 and 0.789, respectively. In men the estimates were 0.702 in VIM I, 0.822 in Fels adults and 0.905 in Fels youth. None of the results from the nine published equations showed R 2 this high in corresponding groups. Conclusions: Our results indicate that several of the Stevens equations have external validity superior to that of nine other published equations among varying age groups, genders and races.